Another Continental Vulture Crisis: Africa's Vultures Collapsing toward Extinction. Issue 2 (18th June 2015) - Ogada, Darcy; Shaw, Phil; Beyers, Rene L.; Buij, Ralph; Murn, Campbell; Thiollay, Jean Marc; Beale, Colin M.; Holdo, Ricardo M.; Pomeroy, Derek; Baker, Neil; Krüger, Sonja C.; Botha, Andre; et al.
Abstract: Vultures provide critical ecosystem services, yet populations of many species have collapsed worldwide. We present the first estimates of a 30‐year Pan‐African vulture decline, confirming that declines have occurred on a scale broadly comparable with those seen in Asia, where the ecological, economic, and human costs are already documented. Populations of eight species we assessed had declined by an average of 62%; seven had declined at a rate of 80% or more over three generations. Of these, at least six appear to qualify for uplisting to Critically Endangered. Africa's vultures are facing a range of specific threats, the most significant of which are poisoning and trade in traditional medicines, which together accounted for 90% of reported deaths. We recommend that national governments urgently enact and enforce legislation to strictly regulate the sale and use of pesticides and poisons, to eliminate the illegal trade in vulture body parts, as food or medicine, and to minimize mortality caused by power lines and wind turbines.